MEMBANGUN KESADARAN MERK UMKM “MPU KERIS” MELALUI DIGITAL BRANDING - Ramadhani, Rakhmad Saiful; Ningsih, Masnia; Syaifuddin, Ahmad (Abdi Panca Marga, 2023)
"Mpu Keris " UMKM in the field of convection and craft production typical of Mojokerto. Until now, these UMKM have several obstacles in competing with similar products from outside Mojokerto, namely; has not yet brought up a characteristic with a strong character to raise typical Mojokerto souvenirs so that it has not gained full trust from the market, especially the people of Mojokerto themselves who have not been interested in buying local products. For this reason, the purpose of this proposed program is to build and strengthen Local products to be more accepted by the community, and it is necessary to develop a pithy promotional strategy so that people accept and are proud in buying local products. The activity program uses a community-based method" which is carried out after obtaining informationthrough in-depth observation and interviews with Partner members, from this information, a strategic plan is prepared in implementing the program. The results of further analysis and discussion about digital branding will be discussed below related to Corporate Identity / Corporate Image, event and experience, content strategy, social media marketing, and point of sale are expected to help Mpu Keris UMKM to achieve success. With a strong identity, unique shopping experience, creative content strategy, effective social media marketing, and diverse sales channels, they have built a brand that inspires and honors the cultural heritage of Majapahit and Mojokerto. In addition, it is important to continuously analyze and measure performance in every aspect of digital branding